A class of integral operators and the Fock space. Issue 4 (2nd April 2016) - Dai, Jineng; Wang, Baobin
Abstract : In this paper, we define a class of integral operators on the space associated with the Fock space. We prove the boundedness and obtain the accurate norm of integral operators. As an application, we give a characterization of the Fock space in several variables.